PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL DISCOVERY LEARNING PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII SMP/ MTS - Pratiwy, Septy Ella; Anggraini, Rini Dian; Yuanita, Putri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The 2013 curriculum is a curriculum that directs students to be actively in the learning process. This research is based on the limited reference of teachers to develop learning devices that are corresponding with the 2013 Curriculum. This research aims to produce learning devices in the form of Syllabus, Learning Implementation Plans (RPP), and Student Worksheets (LKPD) with the Discovery Learning model on the flat side space subject 8th grade student of Junior High School that meet valid and practical requirements. The development model in this research is 4-D with the steps are Define, Design, Develop and Disseminate. The learning device products that have been made are validated by three validators. The average analysis result of the Syllabus validation data is 3.56 in the very valid category which means that the Syllabus is feasible to use and the average value for the RPP is 3.59 and LKPD is 3.64 in the very valid category which means that the RPP and LKPD are worth testing. Valid learning devices have been tested on small groups and large groups. The average results of the analysis of small group trial data is 3.42 and large group trial data is 3.30 which shows a very practical category. The average results of the analysis of observational data on the implementation of learning corresponding to the lesson plan is 2.95, including a very practical category which means that the lesson plan and worksheet are feasible to be used in schools.Key Words: Mathematics Learning Devices, 2013 Curriculum, Discovery Learning, Scientific.